A proposed agricultural credit program for Nigeria : a report for the Consortium for the Study of Nigerian Rural Development - Ohio.; Jones, Ted L.; Gans, A.R.; Robert C. Hoover; Maxey, Richard P.; Stoneham, A.H.; Smith, Nervin C. (East Lansing : Michigan State University, 1966)
This is a report for the consortium for the study of Nigerian development prepared by the agricultural finance center, the Ohio university, in cooperation with the united states agency for international development.
Prepared in cooperation with the United States Agency for International Development.
Includes bibliography.
osa;16/08/18
Loans
Keywords: Agricultural credit; Agriculture